Perlindungan Hukum Bagi Penyedia Jasa Pembiayaan Berbasiskan Elektronik (Peer to peer Landing) Dalam Peraturan OJK NO.77/OJK/01/2016 Tentang Layanan Pinjam Meminjam Uang Berbasis Teknologi Informasi - Miranda Selvy Nasari (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2022)
This study aims to analyze the Legal Protection for Electronic-Based Financing Service Providers (Peer to Peer Landing) in OJK Regulation No.77/Ojk/01/2016 concerning Information Technology-Based Borrowing-Lending Services. The type of research used is a type of research that includes normative legal research. This type of research approach is an approach through legislation (statute approach) and a conceptual approach (conceptual approach). which focuses on the provisions of the legislation that has been enacted. Sources of data obtained from this study based on primary legal sources, secondary data sources and tertiary data sources obtained based on library materials. The results of the study indicate that the Financial Services Authority plays a role in carrying out the regulatory function in protecting peer to peer lending users, specifically regulated regarding peer to peer lending in the Financial Services Authority Regulation Number 77 of 2016 Article 1 Number 3 concerning Information Technology-Based Lending and Borrowing Services ( POJK LPMUBTI). As referred to in decision No.267 NO.267/Pdt.G/2020/PN Bdg that the defendant Budi Santosa made a loan via application/online to PT one stop financially for a year with a loan of Rp.40,000,000 with a payment tenor of one year.